2013
DOI: 10.1016/j.colsurfb.2013.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Solid-support immobilization of a “swing” fusion protein for enhanced glucose oxidase catalytic activity

Abstract: The strategic surface immobilization of a protein can add new functionality to a solid substrate; however, protein activity, e.g., enzymatic activity, can be drastically decreased on immobilization onto a solid surface. The concept of a designed and optimized "molecular interface" is herein introduced in order to address this problem. In this study, molecular interface was designed and constructed with the aim of attaining high enzymatic activity of a solid-surface-immobilized a using the hydrophobin HFBI prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…The immobilization with the fusion protein alone would likely cause a reduction in the laccase activity due to the steric hindrance between single LccC molecules. Previous studies with the class II hydrophobin HFBI fused to a glucose oxidase revealed that a molar ratio between 1:1 and 1:19 of GOx-HFBI to HFBI allowed the highest enzyme activity on surfaces (18). Therefore, we tested different ratios between DewA and the DewA-LccC fusion protein (Fig.…”
Section: ϫ4mentioning
confidence: 99%
See 2 more Smart Citations
“…The immobilization with the fusion protein alone would likely cause a reduction in the laccase activity due to the steric hindrance between single LccC molecules. Previous studies with the class II hydrophobin HFBI fused to a glucose oxidase revealed that a molar ratio between 1:1 and 1:19 of GOx-HFBI to HFBI allowed the highest enzyme activity on surfaces (18). Therefore, we tested different ratios between DewA and the DewA-LccC fusion protein (Fig.…”
Section: ϫ4mentioning
confidence: 99%
“…Since the immobilization was performed with crude culture supernatant containing native exoproteins from A. nidulans, including DewA, it can be assumed that the natural production increase of hydrophobins in the presence of straw (Fig. 2b) was sufficient for effective coating with laccase-fused DewA and did not require additional supplements, as was the case for heterologically produced and purified GOx-HFBI (18).…”
Section: ϫ4mentioning
confidence: 99%
See 1 more Smart Citation
“…This "swingable molecular layer" makes it possible to fuse functional dissociation in a solidmolecular interface or a molecular-liquid interface. Regarding the swingable molecular layer, we have reported on the immobilized enzyme 2 and the affinity sensor using photoexcited current. 3 Charge transfer efficiency i.e., electron transfer, is dependent on the distance through which the electron must travel.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in solution, HFBI forms selforganized membranes at the air/water interface. [9][10][11][12] In this study, we investigated the structural and electrochemical properties of self-organized HFBI membranes on two types of electrode materials. Two requirements must be fulfilled for the selection of substrates.…”
Section: Introductionmentioning
confidence: 99%